Atomic spectrometry update – a review of advances in environmental analysis. Issue 1 (3rd November 2022) - Bacon, Jeffrey R.; Butler, Owen T.; Cairns, Warren R. L.; Cavoura, Olga; Cook, Jennifer M.; Davidson, Christine M.; Mertz-Kraus, Regina
Abstract : This review covers advances in the analysis of air, water, plants, soils and geological materials by a range of atomic spectrometric techniques including atomic emission, absorption, fluorescence and mass spectrometry. Abstract : In the field of air analysis, highlights within this review period included: a new in situ method for measuring resuspended road dust arising from vehicular movements; new ink-printed filter reference materials for black- and elemental-carbon measurements; coupling of a scanning mobility particle sizer to a single-particle-ICP-MS instrument for improved nanoparticle characterisation; developments in total-reflection XRF spectrometry for trace analysis and evaluation of vibrational spectroscopic techniques for measuring respirable crystalline silica in the workplace. The increasing availability of ICP-MS/MS instruments is revolutionising the analysis of environmental samples such as waters for trace elements. The advent of the mass shift mode makes some elements such as P and S much easier to quantify and allows the REEs and some radioisotopes to be determined at much lower concentrations than previously possible. Advances in vapour generation methods are mostly limited to photochemical and chemical vapour generation as reflected in the new table listing the main advances. Solid or liquid phase extraction prior to analysis remains of great interest, although a notable trend is the synthesis of new materials rather than optimisation of commercially available chelating agents and columns. The analytical effort presented in a paper is sometimes much less than the effort put into the synthesis of the materials so one wonders about the likelihood of methods actually being used and results replicated. Notable in the analysis of soils and plants was the unusually large number of review articles – possibly because practical research was hampered by the Covid-19 epidemic. Areas of continued growth were research on nanoparticles, the application of high-resolution continuum source AAS for multielement analysis, the development of miniaturised AES instruments that may ultimately be field-portable and application of LIBS to the analysis of plant materials. A concerted effort to characterise natural minerals that are sufficiently homogeneous to act as reference materials in the microanalysis of geological materials has resulted in the availability of new materials for isotope ratio determinations. Tied to this has been research into U–Pb dating of zircon and a variety of other accessory minerals by LA-ICP-MS and SIMS. New chemometric models have been developed to handle the complex LIBS data arising from the analysis of geological matrices in the field and during ore processing. Studies on the use of ICP-MS/MS to reduce polyatomic interferences in geological applications were widespread, reflecting the availability of such instruments. In contrast, the potential offered by integrating LIBS data with those from LA-ICP-MS has only just started to be explored but is likely to increase with the development of commercial instruments.